Effect of Working Capital Management on Supply Chain Performance and Company Growth in Malaysian Manufacturing Industry - Mohd Haizam Mohd Saudi; R. Wedi Rusmawan Kusumah; R. Adjeng Mariana; Zalina Zainudin (International Journal of Supply Chain Management, 2019)
Manufacturing sector of each country has importance for their economy. Increase or decrease in manufacturing sector performance directly effect on the nation’s economy. In case of Malaysian manufacturing sector, its performance is not in line with Asian region performance. Manufacturing sector performance in Asia is increasing, however, the Malaysian manufacturing sector performance is decreasing. The objective of the current study is to investigate the role of working capital in supply chain performance (SCP) among Malaysian manufacturing companies. A quantitative research approach is used in this study. Primary data were collected on one point of time. A survey was carried out to collect the data. It is found that working capital management has major role in SCP among manufacturing companies. Additionally, positive effect of working capital on SCP increases the company growth.